Glitch art e pure data : utilizando Pure Data para transformar o processo de criação de Glitch em ferramenta - Marques, Daniel Sorrentino (2018)
The interaction of art with thedigitizationofthemediageneratesacomprehensivespectrumofdigital art. Within this spectrum, will lectured on glitch art, a digital art form that works with the intentional introduction of errors in his works of art. Specifically, digital media was studied to make a creative production, using, subverting or listing solutions for artistic creation through computing. We developed a computer program using the visual programming language Pure Data, which transforms the process of creating glitch art into something practical for the artist, showing results that can be explored visually and with less delay. This new method offers less risk of destruction ofthefilesand reduces the computational knowledge load necessary to cause a failure with artistic intention. Additionally, we investigate the possibilities that this glitch facilitator creates for new interactions within the two fields of knowledge focused on this project: art and computing.